Making Regulatory Impact Assessment Gender-Sensitive: The Case of the Czech Republic and Slovakia - Katarina STAROŇOVÁ; Eva HEJZLAROVÁ; Kristýna HONDLÍKOVÁ (Transylvanian Review of Administrative Sciences, 2017)
Gender Impact Assessment (GIA) has beeninstitutionalized in different ways in the Czechand Slovak Republics; the Czech Republic introducedGIA independently of regulatory impactassessment (RIA) process relatively earlyon, while Slovakia did so only during the modernizationof RIA processes in the early 2010s.Based on the analysis of 671 RIAs from 2007 to2015 the study fi nds that with a few exceptionslargely coming from the Ministries of Social Affairswhere gender equality units were originallyanchored in both countries, the GIA responsesare relatively formal and ‘blind’. This is despitethe obligations and RIA modernization processesin both countries which introduced also standardizationand supervision of RIA processesby independent bodies. Both countries witnesspersistent invisibility of gender, despite differentGIA trajectories which can be attributed to thedominance of economists in both RIA processes.